Teachers’ Perceptions towards the implementation of Neuro-Linguistics Programming (NLP) Techniques in Teaching Speaking at Indonesian Senior High School Context - Asia Masita Haidir; Syarifuddin Dollah; Muhammad Basri (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study examines teachers’ perceptions of Neuro-Linguistic Programming (NLP) in teaching speaking within Indonesian senior high schools. A qualitative design was employed, using purposive sampling to select three English teachers. Data were collected through interviews and analyzed thematically. The findings indicate that teachers held a clear understanding of NLP as an approach linking language, cognition, and behavior. They expressed positive attitudes toward its implementation, identifying techniques such as pacing, modeling, elicitation, visualization, anchoring, and reframing as effective in fostering interactive classrooms, lowering anxiety, and enhancing students’ confidence. Teachers also acknowledged challenges, particularly large class sizes, limited instructional time, and cultural factors that influenced classroom dynamics. The primary motivation for applying NLP was to overcome affective barriers such as low self-confidence and fear of mistakes considered more problematic than linguistic limitations. Overall, NLP was perceived to enrich speaking instruction by addressing both cognitive and affective aspects of learning. It provides a holistic framework that supports learner-centered, engaging, and confidence-building English speaking classrooms.